Holocene Population Decline and Conservation Implication for the Western Hercules Beetle, Dynastes grantii (Coleoptera, Scarabaeidae). (28th May 2019) - Huang, Jen-Pan
Abstract: The Western Hercules beetle ( Dynastes grantii ) is endemic to the highland forest habitats of southwestern United States and northern Mexico. The habitats harbor many endemic species, but are being threatened by rapid climate change and urban development. In this study, the genetic structure of D. grantii populations from southwestern United States was investigated. Specifically, genomic data from double-digest restriction-site-associated DNA sequencing libraries were utilized to test whether geographically distant populations from the Mogollon Rim (Arizona [ N = 12 individuals] and New Mexico [ N = 10 individuals]) are genetically structured. The study also estimated the effective population size of the Mogollon Rim populations based on genetic diversity. The results indicated that the 2 geographic populations from the Mogollon Rim were not genetically structured. A population size reduction was detected since the end of the last glacial period, which coincided with a reduction of forest habitat in the study area. The results implied that the connectivity and the size of highland forest habitats in the Mogollon Rim could have been the major factors shaping the population genetic structure and demographic history of D. grantii . The Western Hercules beetle could be a useful flagship species for local natural history education and to promote the conservation of highland forest habitats.